2006
DOI: 10.1182/blood-2006-06-028704
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors and their ligands control mesenchymal stem cell functions

Abstract: IntroductionMesenchymal stem cells (MSCs) comprise an adult population that resides in many organs and exhibits multiple functions and phenotypes upon in vitro culture; MSCs can be induced to differentiate into mesodermal cell lineages, 1,2 support and regulate hematopoiesis, [3][4][5][6][7] regulate the stem-cell niche, [8][9][10][11][12] and may participate in the repair of tissue damage inflicted by normal wear and tear, injury, or disease. [13][14][15][16] MSCs comprise 0.01% to 0.001% of the bone marrow (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
409
1
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(451 citation statements)
references
References 93 publications
29
409
1
8
Order By: Relevance
“…4A, 4C, and 6C). These results are in line with another study in mMSC [35]. As in human MSC [19], TLR3 and TLR4 are expressed at levels comparable to DC (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…4A, 4C, and 6C). These results are in line with another study in mMSC [35]. As in human MSC [19], TLR3 and TLR4 are expressed at levels comparable to DC (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…The low activation of NFkB detected in GICs suggests that NFkB may be dispensable for survival and proliferation of these tumor NFjB blockade promotes senescence of differentiating GICs L Nogueira et al progenitor cells, which correlates with data showing that p65 immunoreactivity is abundant in the cytoplasm of the majority of cells within neurospheres derived from embryonic mouse brain, but only occasional weak nuclear localization (active state) is detected (Young et al, 2006). NFkB has been described to function as an inducer and an inhibitor of differentiation, which reflects its heterogeneity in activities depending on the cell system studied (Zhang et al, 1998;Li and Makarov, 2006;Pevsner-Fischer et al, 2007;Vaira et al, 2008). We showed that blockade of NFkB by using genetic strategies or small-molecule inhibitors accelerate maturation of differentiating GICs.…”
Section: Discussionsupporting
confidence: 67%
“…The secretion of these factors from MSCs has been shown to be induced by IFN-γ alone, or in combination with tumor necrosis factor (TNF)-α, IL-1α, or IL-1β [23]. Toll-like receptors (TLR) also have been reported to be expressed on MSCs and to trigger the induction of cytokines and chemokines [24]. Thus, various and complicated mechanisms are involved with immunomodulatory properties of MSCs.…”
Section: Immunomodulatory Function Of Mscsmentioning
confidence: 99%